Step
*
of Lemma
bag-summation-equal-implies-all-equal-1
∀[T:Type]. ∀[b:bag(T)]. ∀[f,g:T ⟶ ℤ].
  (∀x:T. (x ↓∈ b 
⇒ (f[x] = g[x] ∈ ℤ))) supposing ((Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]) and (∀x:T. (x ↓∈ b 
⇒ (f[x] ≤ g[x]))))
BY
{ ((Assert Assoc(ℤ;λx,y. (x + y)) ∧ Comm(ℤ;λx,y. (x + y)) BY
          (RepeatFor 2 (D 0) THEN Reduce 0 THEN Auto))
   THEN Auto
   THEN BagToList 4
   THEN Auto) }
1
1. Assoc(ℤ;λx,y. (x + y))
2. Comm(ℤ;λx,y. (x + y))
3. T : Type
4. b : T List
5. f : T ⟶ ℤ
6. g : T ⟶ ℤ
7. ∀x:T. (x ↓∈ b 
⇒ (f[x] ≤ g[x]))
8. Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]
9. x : T
10. x ↓∈ b
⊢ f[x] = g[x] ∈ ℤ
Latex:
Latex:
\mforall{}[T:Type].  \mforall{}[b:bag(T)].  \mforall{}[f,g:T  {}\mrightarrow{}  \mBbbZ{}].
    (\mforall{}x:T.  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  =  g[x])))  supposing 
          ((\mSigma{}(x\mmember{}b).  g[x]  \mleq{}  \mSigma{}(x\mmember{}b).  f[x])  and 
          (\mforall{}x:T.  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  \mleq{}  g[x]))))
By
Latex:
((Assert  Assoc(\mBbbZ{};\mlambda{}x,y.  (x  +  y))  \mwedge{}  Comm(\mBbbZ{};\mlambda{}x,y.  (x  +  y))  BY
                (RepeatFor  2  (D  0)  THEN  Reduce  0  THEN  Auto))
  THEN  Auto
  THEN  BagToList  4
  THEN  Auto)
Home
Index